Effects of subject-area degree and classroom experience on new chemistry teachers' subject matter knowledge - Nixon, Ryan S.; Campbell, Benjamin K.; Luft, Julie A. (International journal of science education, 2016)
Science teachers need to understand the subject matter they teach. While subject matter knowledge (SMK) can improve with classroom teaching experience, it is problematic that many secondary science teachers leave the profession before garnering extensive classroom experience. Furthermore, many new science teachers are assigned to teach science subjects for which they do not hold a degree. This study investigates the SMK of new secondary science teachers assigned to teach chemistry in their first three years of teaching. These new teachers do not have the advantage of years of experience to develop their SMK and half hold a degree in biology rather than chemistry. This qualitative study explores the effects of holding a degree in the subject area one teaches as well as classroom teaching experience on teachers' SMK for two chemistry topics, conservation of mass and chemical equilibrium. Qualitative analysis of semi-structured interviews indicated that the SMK of teachers who had a chemistry degree and more extensive classroom experience was more coherent, chemistry-focused, and sophisticated than that of teachers who lacked this preparation and experience. This study provides evidence that new science teachers' SMK is influenced by both holding a degree in the subject area and having classroom experience.